Oscillatory Coupling Between Neural and Cardiac Rhythms - Sargent, Kaia S.; Martinez, Emily L.; Reed, Alexandra C.; Guha, Anika; Bartholomew, Morgan E.; Diehl, Caroline K.; Chang, Christine S.; Salama, Sarah; Popov, Tzvetan; Thayer, Julian F.; Miller, Gregory A.; Yee, Cindy M. (Psychological Science, 2024)
Oscillations serve a critical role in organizing biological systems. In the brain, oscillatory coupling is a fundamental mechanism of communication. The possibility that neural oscillations interact directly with slower physiological rhythms (e.g., heart rate, respiration) is largely unexplored and may have important implications for psychological functioning. Oscillations in heart rate, an aspect of heart rate variability (HRV), show remarkably robust associations with psychological health. Mather and Thayer proposed coupling between high-frequency HRV (HF-HRV) and neural oscillations as a mechanism that partially accounts for such relationships. We tested this hypothesis by measuring phase-amplitude coupling between HF-HRV and neural oscillations in 37 healthy adults at rest. Robust coupling was detected in all frequency bands. Granger causality analyses indicated stronger heart-to-brain than brain-to-heart effects in all frequency bands except gamma. These findings suggest that cardiac rhythms play a causal role in modulating neural oscillations, which may have important implications for mental health.